Uji Efektivitas Ekstrak Etanol Kulit Batang Kersen (Muntingia calabura L.) Sebagai Antidiabetes Pada Mencit Jantan - Endah Nurrohwinta Djuwarno; Widy Susanti Abdulkadir; Febriyaningsi Radjak (Jambura Journal of Chemistry, 2022)
Diabetes is a degenerative disease characterized by high levels of glucose in the blood. Diabetes can lead to complications if left untreated. Treatment of diabetes can be done pharmacologically (using traditional medicines or synthetic) or non- pharmacologically (accustoming a healthy lifestyle). The use of traditional medicines is relatively cheap compared to synthetic drigs so that can be used as an anti-diabetic is the Jamaica Cherry (Muntingia calabura L.), as it contains secondary metabolites tha act as antidiabetics. Therefore, this present research aimed to determine the as an antidiabetic in male mice. The research methods used were maceration, phytochemical screening, anti-diabetic test with pre test and post test control design methods to determine if there was a decrease after the administration of the extract. The finding depicted that in the phytochemical screening test, it was observable that Jamaica Cherry (Muntingia calabura L.) bark contained secondary metabolites, incluiding alkaloids, flavonoids, and tannins, while the antidiabetic test indicated that all four extract with concentration of 50 mg, 100 mg, 200 mg and 400 mg were effective to reduce the blood sugar level with each percentage of 9%, 16%, 26%, and 42%. In brief, the antidiabetic compounds that play a role in the ethanol extract of Jamaica Cherry (Muntingia calabura L.) bark were flavonoids and tannins.